An Erythropoietin-Independent Mechanism of Erythrocytic Precursor Proliferation Underlies Hypoxia Tolerance in Sea Nomads - Ilardo, Melissa; dos Santos, Maria C. Ferreira; Grote Beverborg, Niels; Rajan, Malini; Said, M. Abdullah; Verweij, Niek; Van Der Harst, Pim; Van Der Meer, Peter; Leibold, Elizabeth A. (Frontiers in Physiology, 2022)
The Bajau Sea Nomads were recently demonstrated to have evolved larger spleens as an adaptation to millennia of a marine foraging lifestyle. The large-spleen phenotype appears to derive from increases in thyroid hormone (TH) production as a result of reduced expression of phosphodiesterase 10A (PDE10A), though the exact mechanism remains unknown. Through pharmacological inhibition of PDE10A using the selective inhibitor MP-10 in mice, we were able to mimic the Bajau adaptation and show that treated mice had significantly larger spleens than control animals. This difference appears connected to an excess of early stage erythrocytes and an apparent increase in red blood cell (RBC) proliferation in response to increased TH. However, we determined that the stimulation of RBC production in the mouse model via TH is Erythropoietin (Epo)-independent, unlike in the altitude (chronic hypoxemia) response. We confirmed this using human GWAS data; although the Bajau PDE10A variants are significantly associated with increased TH levels and RBC count, they are not associated with Epo levels, nor are other strongly thyroid-associated SNPs. We therefore suggest that an Epo-independent mechanism of stimulating RBC proliferation via TH upregulation underlies the increase in spleen size observed in Sea Nomad populations.